ANALISIS KINERJA UMKM DENGAN PENDEKATAN BALANCED SCORECARD: STUDI PADA TWISTEA INDONESIA PURWOKERTO - D. Inka Aprilia; Lutfiyah Wahyu Sani; Safira Kamilah Abdillah; Yoiz Shofwa Shafrani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the performance of Twistea Indonesia Purwokerto using the Balanced Scorecard approach. This study uses a descriptive qualitative method with data collected through interviews and observations. The analysis is conducted based on four Balanced Scorecard perspectives, namely the financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The results show that Twistea Indonesia Purwokerto has relatively good business performance, reflected in increased sales and revenue, positive customer responses, effective operational processes and product innovation, as well as solid teamwork and effective employee training. It can be concluded that the Balanced Scorecard provides a comprehensive framework for evaluating business performance and supports MSME development in facing business competition.